Analysis of public administrative reforms: a case in Afghanistan / Niaz Mohammad Hamdard and Mohammad Jamal Shenwary - Hamdard, Niaz Mohammad; Shenwary, Mohammad Jamal (UiTM Cawangan Johor, 2019)
During the era of transition until now, Afghanistan has been making steady progression in the form of growth. The Bonn Conference (2001) established in gesticulation a series of policy frameworks by introducing much operative civil service one of preferences of the Afghan government. The Afghan National Unity Government introduced reforms program so called "Realizing Self Reliance" in December 2014, as a result of Kabul and London Conferences upon Afghanistan by marking the commencement of "decade of transformation" (2014-2025). This study is qualitative in nature and the data were collected through secondary sources including various reports and newsletter from year 2002 to 2018 to attain the objective of this study. The current study reviews the local governance reforms in Afghanistan based on Afghan Government and international donors. This study highlights the reforms made by Independent Administrative Reforms and Civil Services Commission (IARCSC) and Independent Directorate of Local Governance. They have presented numerous reformed policies, programs, laws, regulations, and projects to address the issues in local since its inception. Priority Restructuring and Reform (PRR) program is one of them which was announced by IARCSC to backing more salaries for the crew of government, Sub--‐ National Governance Policy of IDLG sanctioned by the cabinet in 2010, primer of District Delivery Program (DDP) by IDLG, and the National Priority Program (NPP) for Local Governance and the NPP. These acts emphasize on refining local government in Afghanistan. The principal aim of NPP is to strengthen and promote leadership, institutional, organizational, administrative and individual capacities for governance at both central and local levels to enable service delivery, economic growth, justice, stabilization and security. These reforms will be applied by numerous government departments. The IARCSC grasps the central position in execution of NPP. The current study presents the short and long term policy recommendation at the district and provincial level to accomplish the goal of growth and development. This study is very significant for the Afghan government's official at central, provincial and district level as it provide the ways to overcome various issues which exist at local governance level.